Loneliness in overseas students: reviewed from father nurturance - Sanjaya, Ersa Lanang; Dorkas, Mopheta Audiola (Intelektual Pustaka Media Utama, 2024)
The uneven condition of education in Indonesia has led to the phenomenon of overseas students. This phenomenon is an effort made by prospective students to obtain higher quality education or more according to their interests. Students who migrate certainly face bigger challenges, one of which is loneliness. Many studies reveal that the negative impact of feelings of loneliness experienced by a person, so it requires further study. The main objective of this study is to see how father nurturance influences loneliness among overseas students. This study used a quantitative approach with a total of 107 respondents. From this study, it was found that the role of the father has a significant influence on feelings of loneliness experienced by overseas students.